Quantum effects due to a moving Dirichlet point - Fosco, Cesar Daniel (2020)
We study quantum effects induced by a pointlike object that imposes Dirichlet boundary conditions along its worldline, on a real scalar field φ in 1, 2, and 3 spatial dimensions. The boundary conditions result from the strong coupling limit of a term quadratic in the field and localized on the particle's trajectory. We discuss the renormalization issues that appear and evaluate the effective action. Special attention is paid to the case of two spatial dimensions where the coupling constant is adimensional.